2011
DOI: 10.1093/carcin/bgr284
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral health and gastric precancerous lesions

Abstract: Although recent studies have suggested that tooth loss is positively related to the risk of gastric non-cardia cancer, the underlying oral health conditions potentially responsible for the association remain unknown. We investigated whether clinical and behavioral measures of oral health are associated with the risk of gastric precancerous lesions. We conducted a cross-sectional study of 131 patients undergoing upper gastrointestinal endoscopy. Cases were defined as those with gastric precancerous lesions incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 30 publications
4
53
0
3
Order By: Relevance
“…We have previously reported a significant positive association between active gingival bleeding and presence of gastric precancerous lesions in a cross-sectional study of an endoscopic population [20], consistent with the hypothesis that periodontal disease may increase the risk of gastric cancer. However, these studies lack information on specific oral pathogens necessary to elucidate the role of oral health in gastric cancer development.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…We have previously reported a significant positive association between active gingival bleeding and presence of gastric precancerous lesions in a cross-sectional study of an endoscopic population [20], consistent with the hypothesis that periodontal disease may increase the risk of gastric cancer. However, these studies lack information on specific oral pathogens necessary to elucidate the role of oral health in gastric cancer development.…”
Section: Introductionsupporting
confidence: 84%
“…A detailed description of the study has been presented elsewhere [20]. Briefly, subjects ≥40 years of age undergoing an upper endoscopy at Bellevue Hospital Center in New York City were invited to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, other potential factors related to neighborhood SES that might also explain differing H. pylori prevalence—such as sanitation practices, water source, refrigeration, and cooking and eating habits—were not accounted for, although these factors are most likely also associated with individual- and neighborhood-level education and income categories. It has also been suggested that poor oral health is associated with gastric cancer [30] and precancerous lesions [31], although the association with H. pylori infection specifically has not been found to be significant above and beyond individual SES parameters [32, 33]. Unfortunately, we did not have sufficient data on oral health to address this question in our population.…”
Section: Discussionmentioning
confidence: 82%